High‐definition optical coherence tomography of melanocytic skin lesions. Issue 8 (18th September 2014) - Gambichler, Thilo; Plura, Iris; Schmid‐Wendtner, Monika; Valavanis, Konstantinos; Kulichova, Daniela; Stücker, Markus; Pljakic, Azem; Berking, Carola; Maier, Tanja
Abstract : High‐definition optical coherence tomography (HD‐OCT) scanners have recently been developed. We assessed micromorphological HD‐OCT correlates of benign naevi (BN) and malignant melanoma (MM). 28 BN and 20 MM were studied using HD‐OCT and histology. Epidermal honeycomb/cobblestone pattern, regular junctional cell nests, and edged papillae are more often observed in BN, whereas fusion of rete ridges, pagetoid cells and junctional and/or dermal nests with atypical cells are more frequently seen in MM. A high overlap of HD‐OCT features in BN and MM was observed and in 20% of MM we did not find evidence for malignancy in OCT images at all. Using HD‐OCT it is possible to visualize architectural and cellular alterations of melanocytic skin lesions. The overlap of HD‐OCT features seen in BN and MM and the absence of suspicious HD‐OCT features in some MM represents an important limitation of HD‐OCT affecting the sensitivity of HD‐OCT in diagnosing MM.High‐definition optical coherence tomography and the corresponding vertically sectioned histology of a compound naevus. Abstract : Micromorphological high‐definition optical coherence tomography (HD‐OCT) correlates of benign naevi (BN) and malignant melanoma (MM) are assessed. Epidermal honeycomb/cobblestone pattern, regular junctional cell nests, and edged papillae are more often observed in BN, whereas fusion of rete ridges, pagetoid cells and junctional and/or dermal nests with atypical cells are more frequently seen in MM. Using HD‐OCT, architectural and cellular alterations of melanocytic skin lesions (MSL) can be visualized.